2012
DOI: 10.1007/s10853-012-6633-6
|View full text |Cite
|
Sign up to set email alerts
|

On depression of glass transition temperature of epoxy nanocomposites

Abstract: Epoxy composite materials filled with nanoalumina particles were prepared by mechanical mixing techniques. The glass transition temperatures (T g ) of the nanocomposites were found to decline significantly with the increasing filler content. After the addition of 30-phr nanoparticles, the T g of the filled sample decreased by as high as 55°C, as compared with that of the neat epoxy polymer. Based on the selective adsorption hypothesis and the molecular diffusion, it is speculated that the hardener molecules we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Depressing of T g has been observed before in inorganic nanoparticle-reinforced epoxy composite systems. 34,[36][37][38] Tang and Weder also observed depressing of T g at low CNC content in aromatic hardener-cured epoxy. 25 However, T g of the cured epoxy increased when the CNC content increased, as the CNC formed a rigid percolation network, which limited the movment of polymer chains.…”
Section: Green Materialsmentioning
confidence: 79%
See 1 more Smart Citation
“…Depressing of T g has been observed before in inorganic nanoparticle-reinforced epoxy composite systems. 34,[36][37][38] Tang and Weder also observed depressing of T g at low CNC content in aromatic hardener-cured epoxy. 25 However, T g of the cured epoxy increased when the CNC content increased, as the CNC formed a rigid percolation network, which limited the movment of polymer chains.…”
Section: Green Materialsmentioning
confidence: 79%
“…32 In addition, Liu et al suggested that nanoparticles could also selectively absorb resin or hardener at their surface, thus limiting the reaction between the epoxy resin and hardener. 36 In this study, since CNC was exposed with hardener first, the weak hydrogen bonding interactions between the CNCs and hardeners could possibly inhibit the epoxy/hardener reaction. These weak interactions of the hardeners, acetone, and CNCs could have caused incomplete curing in some regions of the epoxy and led to the formation of inhomogeneous crosslinking networks.…”
Section: Green Materialsmentioning
confidence: 90%
“…The observed T g trend could be due to the occurrence of two concurrent phenomena: as the filler content increases the chain blocking effect is more effective and induces a slight T g increase, while, at the same time, polymer-filler chemical interactions and the viscosity increase reduces the crosslinking degree of the matrix, with a consequent T g drop. In a recent investigation on epoxy/alumina nanocomposites, Liu et al [38] speculated that the hardener molecules were unevenly distributed at a microscale, thus leading to a stoichiometric imbalance between epoxy components and reduced T g values.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…As already reported in our previous paper on similar epoxy systems , the observed T g trend could be due to the occurrence of two concurrent phenomena: as the filler content increases the chain blocking mechanisms is more effective and leads to a slight T g increase, while, at the same time, polymer‐filler chemical interactions and the viscosity increase reduces the crosslinking degree of the matrix, thus reducing the T g of the material. As recently reported by Liu et al on epoxy/alumina nanocomposites, the hardener molecules were unevenly distributed at a microscale, leading to a stoichiometric imbalance between epoxy components and reduced T g values.…”
Section: Resultsmentioning
confidence: 51%